2011
DOI: 10.1002/dvdy.22599
|View full text |Cite
|
Sign up to set email alerts
|

A transgenic wnt8a:PAC reporter reveals biphasic regulation of vertebrate mesoderm development

Abstract: Vertebrate wnt8a links anteroposterior and dorsoventral axis patterning, but the regulation of wnt8a expression and its relationship to mesoderm induction and maintenance pathways is unclear. To address this, we have generated zebrafish transgenic for a modified genomic PAC clone that expresses EGFP from the wnt8a locus. The EGFP reporter transgene is expressed in a pattern nearly identical to wnt8a, including maternal deposition, expression in the ventrolateral mesoderm and in the yolk syncytial layer. Loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…We previously generated a wnt8aPA-C:EGFP transgenic line in which bright EGFP labeling of several mesodermally derived organs, including somites, YSL, pronephros, heart, and blood, is observed despite the absence of transcripts at that stage (Narayanan et al, 2011). Thus, EGFP fluorescence in these tissues at 24 hpf, especially in somites and YSL, is a convenient assay to determine whether reporter constructs are active in the precursors of these tissues.…”
Section: Cis-analysis Reveals Multiple Wnt8a1 Regulatory Elementsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously generated a wnt8aPA-C:EGFP transgenic line in which bright EGFP labeling of several mesodermally derived organs, including somites, YSL, pronephros, heart, and blood, is observed despite the absence of transcripts at that stage (Narayanan et al, 2011). Thus, EGFP fluorescence in these tissues at 24 hpf, especially in somites and YSL, is a convenient assay to determine whether reporter constructs are active in the precursors of these tissues.…”
Section: Cis-analysis Reveals Multiple Wnt8a1 Regulatory Elementsmentioning
confidence: 99%
“…We recently demonstrated that zebrafish wnt8a.1 is regulated in a biphasic manner via cis-elements within an 80-KB genomic interval (Narayanan et al, 2011). This biphasic regulation correlates with the transition from Nodal-dependent mesoderm induction to Ntl-dependent posterior growth.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations